2009
DOI: 10.1136/emj.2007.051656
|View full text |Cite
|
Sign up to set email alerts
|

Predicting patient arrivals to an accident and emergency department

Abstract: The two separate arrival streams exhibit different statistical characteristics and so require separate time series models. It was only possible to accurately characterise and forecast walk-in arrivals; however, these model forecasts will still assist hospital managers at the case study hospital to best use the resources available and anticipate periods of high demand since walk-in arrivals account for the majority of arrivals into the A&E department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…A number of authors have therefore fitted and tested nonhomogeneous Poisson models to patient arrival processes for example, (1) Barnett et al [2002] for intensive care admissions and daily variations in the Poisson rate; (2) Shanmugam et al [2007] have used Poisson regression to fit a nonhomogeneous Poisson process to stroke incidence data; (3) Harrison et al [2005] for intensive care admissions and daily variations in the Poisson rate; and (4) Alexopoulos et al [2008] for patient arrivals at community clinics. Also, a number of authors distinguish between emergency (unscheduled) and scheduled arrivals for example, Alexopoulos et al [2008] and Au-Yeung et al [2009]. In the latter case, it is unlikely that arrivals are random while unscheduled arrivals may be subject to effects of grouping of arrivals, fluctuations by time of day, and dependence between arrivals in different periods of the day [Alexopoulos et al 2008].…”
Section: Methodsmentioning
confidence: 99%
“…A number of authors have therefore fitted and tested nonhomogeneous Poisson models to patient arrival processes for example, (1) Barnett et al [2002] for intensive care admissions and daily variations in the Poisson rate; (2) Shanmugam et al [2007] have used Poisson regression to fit a nonhomogeneous Poisson process to stroke incidence data; (3) Harrison et al [2005] for intensive care admissions and daily variations in the Poisson rate; and (4) Alexopoulos et al [2008] for patient arrivals at community clinics. Also, a number of authors distinguish between emergency (unscheduled) and scheduled arrivals for example, Alexopoulos et al [2008] and Au-Yeung et al [2009]. In the latter case, it is unlikely that arrivals are random while unscheduled arrivals may be subject to effects of grouping of arrivals, fluctuations by time of day, and dependence between arrivals in different periods of the day [Alexopoulos et al 2008].…”
Section: Methodsmentioning
confidence: 99%
“…A key concern is the issue of validation of these models. Some known systems, with many users, have been modeled, strategies have been adopted that are not supported by smart environments (see, for example [1]) and their results have been compared with real observations. A future issue is to develop these empirical analyses in relation to the proposed smart environments.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Variable selection was consistent with previous research. 18,21,22,[26][27][28]30,31 Some authors found evidence of the effects of weatherrelated factors for specific pathologic findings [32][33][34][35][36] ; however, these cannot be obtained with sufficient accuracy in advance and most often have little effect on total visits. 18,21 The dependent variable was the total number of ED visits, which was then transformed into staffing requirements.…”
Section: Variablesmentioning
confidence: 99%
“…Also, most often, monthly 25 or daily visits were predicted. 21,22,[26][27][28][29] Because nursing personnel is usually organized in 8-hour shifts, daily predictions are of little use for realistic staff planning. Patient arrival volume often varies dramatically between these shifts, as fewer patients seek ED care at night or during morning working hours than during the afternoon shift.…”
mentioning
confidence: 99%